HUBUNGAN KUALITAS SUMBER DAYA MANUSIA TERHADAP PENINGKATAN KINERJA ORGANISASI PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) KOTA SIBOLGA - Fauziah Nur Simamora; Rifka Hadia Lubis; Rosmita Ambarita (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to determine the quality of human resources towards improving organizational performance at the Regional Drinking Water Company (PDAM) of Sibolga City. respondents. In this study, several tests were carried out which aimed to determine the relationship and influence between the implementation of the quality of human resources on improving organizational performance, namely between the quality of human resources and the company's performance at the Tirta Nauli Sibolga Regional Drinking Water Company, there is a positive influence and relationship.,From the results discussion of normality using Histogram Analysis, shows that the regression model cannot assume normality assumptions, namely forming a histogram chart and organizational performance can have a normal level, From the results of the validity calculation, each item variable X and Y Corrected Item Total value of r count is more than the value of r table (0.266). Thus, all of the variables X and Y are declared valid. From the results of the reliability test calculation, the variables X and Y can be said to be reliable because the Cronbach's Alpha value > r is critical. The calculation of the coefficient of determination obtained is 51.84% and the remaining 48.16% is determined by other factors not discussed in this study, such as leadership, motivation, infrastructure, communication and others. From the calculation of the linear regression line, the variables X and Y variables are: Y = 6.10 + 0.92 X. In this case, the X (HR quality) variable and Y (organizational performance) are in a positive direction, meaning that if the X value (quality HR) = zero, then the Y variable (organizational performance) = 6.10 and From the hypothesis test carried out, by comparing the t-count value with the t-table value, it can be seen that the t-count value is greater than ttable (7.409 > 2.009), this means that the accepted hypothesis is the alternative hypothesis (Ha). Keywords : quality of human resources, improvement of organizational performance